Utilização de sistemas de energia elétrica de corrente alternada com arduino: uma sequência didática para a aprendizagem de conceitos de eletrodinâmica - TINOCO, Vicente de Paula Almeida (2024)
The teaching of science-related subjects in basic education schools often poses a challenge, motivating educators to seek alternatives to facilitate learning in the face of encountered difficulties. Physics, as an experimental science, requires experimentation for its teaching. However, many schools lack laboratories and specific practices. In this context, we propose the creation of an educational resource aimed at understanding the concepts of electrodynamics, based on Jean Piaget's Constructivist theory and Seymour Papert's Constructionist theory. This resource was developed in collaboration with 3rd-year high school students at CE Paulo Ramos School, located in Turiaçu - MA. The proposal includes an experimental kit that comprises a model of an electrical energy distribution system, demonstrating the function and applications of alternating current in an investigative manner. The model allowed students to grasp how monophasic, biphasic, and triphasic connections work conceptually and in practice, as well as the significance of electrical components like generators, transformers, and voltage sources in a circuit. The implementation of this educational resource followed a didactic sequence consisting of 10 sessions, divided into 5 stages: assessment of students' prior knowledge on the subject, introduction of initial problems, knowledge organization, practical application of knowledge, and verification of students' knowledge acquisition. After collecting the evaluation data, progress in relation to the established learning objectives in the didactic sequence is assessed through formative evaluation, tests, engagement, peer assessment, and self assessment.